ENVIRONMENT AND OVER POPULATION: THE HEALTH AND SOCIAL IMPUCATIONS - EKOKOR, O. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2015)
This paper attempted to highlight the health and social implications 01 overpopulation in the environment. Some of the health and social problems associated with an overpopulated environment include air pollution, (with /, resultant respiratory diseases such as bronchitis), overcrowding, food ana water shortages, unemployment, thuggery and so on. Recommendations made among others include more sensitization or health education of the people' on the need to check overpopulation by embracing family planning, protectable, the environment from danger and individuals protecting themselves too from the environmental dangers such as air pollution.